Changing ICT Rankings of African Nations - Kelly, Tim (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2004)
After years of being an information and communication technology laggard relative to other developing regions of the world, Africa has been pushed to the forefront in a new information revolution, thanks to mobile communications. This period has also witnessed considerable mobility in the information and communication technology rankings of different African nations. This article examines changes in the information and communication technology rankings of different African nations and concludes that, as an analytical framework, the “digital divide” does not accurately describe what is happening on the continent and may lead to policy choices that are harmful to Africa’s future.